Patterns of maternal adverse childhood experiences and the intergenerational association of preschool children’s emotional and behavioral problems - Li, Ruoyu; Xiao, Wan; Wu, Jun; Zhou, Yang; Zha, Jinhong; Wang, Danni; Xing, Tian; Wan, Yuhui (Frontiers in Psychiatry, 2024)
Introduction: Children of whose mothers exposed to adverse childhood experiences (ACEs) are at increased risk for developmental problems. This study aims to investigate the relationship between types and patterns of maternal ACEs and preschool children’s emotional and behavioral problems (EBPs) in China, and to explore gender differences associated with these problems. Methods: In this cross-sectional study, we selected 9,647 children from 36 preschools in three cities of Anhui province, China. Questionnaires were used to report the details of maternal ACEs and children’s EBPs. We used the latent class analysis (LCA) to identify “patterns” in the types of maternal ACEs. Binomial logistic regressions was performed to examine the relationship between types and patterns of maternal ACEs and preschoolers’ EBPs. Results: Latent class analysis (LCA) revealed four different classes of maternal ACEs. Logistic regression analysis showed that compared with the low ACEs class, children of mothers in the high abuse and neglect class had the highest risk of developing EBPs (OR = 5.93, 95%CI: 4.70-7.49), followed by moderate ACEs class (OR = 2.44, 95%CI: 1.98-3.00), and high household dysfunction class (OR = 2.16, 95%CI: 1.19-3.90). We found gender differences in the effects of high abuse and neglect/moderate ACEs class and maternal childhood physical abuse/neglect on children’s EBPs, which had a stronger impact on EBPs in boys than girls (P＜0.05). Discussion: This study supports and refines existing research that confirms an intergenerational association between types and patterns of maternal ACEs and children’s EBPs in a large Chinese sample, so as to provide references for the early prevention and control of children’s EBPs.